ANALISIS PUTUSAN HAKIM TERHADAP PERBUATAN TINDAK PIDANA KORUPSI PERBANKAN YANG DAPAT MERUGIKAN KEUANGAN NEGARA ATAU PEREKONOMIAN NEGARA ( Studi Putusan Nomor : 29/Pid.Sus-TPK/2025/PN Bdg ) - Dendi Ramdani Muslim; Syahrul Anwar; Suradi (PT. Saha Kreasi Indonesia, 2025)
The distribution of People's Business Credit (KUR) funds in Indonesia is a flagship government programme to encourage the development of MSMEs. However, in practice, there have been cases of misuse of funds that have caused losses to the state finances, such as the incident in Tasikmalaya, where a former Bank Rakyat Indonesia (BRI) clerk was involved in fake credit fraud. This study aims to evaluate the causes and effects of KUR fund misuse and the role of supervision in preventing such incidents. Various internal factors within banks, such as a lack of monitoring of credit verification and evaluation procedures, coupled with external factors such as economic uncertainty and fierce business competition, further exacerbate the quality of fund distribution. The implementation of stricter Good Corporate Governance (GCG) principles in banks that distribute KUR is expected to improve management and reduce misuse. Recommendations for improvement include increasing transparency, tightening supervision, and providing continuous education for MSME actors and bank officers.